Pengaruh Penambahan Bahan Redam pada Kebocoran Alat Ukur Daya Isolasi Bahan: Didiek Basuki Rahmat, Alpha Hambally Armen, Gontjang Prajitno - Didiek Basuki Rachmad, Didiek Basuki Rachmad; Alpha Hambally Armen, Alpha Hambally Armen; Gontjang Prajitno, Gontjang Prajitno (Jurnal Fisika dan Aplikasinya, 2025)
A study has been done that is adding damping materials to reduce leakage power gauge insulation materials. This instrument can determine the value of Insertion Loss and Noise Reduction of a material. This study was conducted a box-making are designed to cover all parts of insulating material power gauge, the box is made of gypsum is added to the combination of damping material that is rockwoll and rugs, machine condition before, the leakage rate of the tool reaches 24 dB - 33 dB, with the box, the rate of leakage can be reduced in accordance. The three variations of damping materials are carpets, rugs plus rockwollrockwoll and leakage values can be minimized by the use of damping carpet plus rockwoll reaches 5 dB - 15 dB. Insulation materials of power measuring devices can perform measurements with the noise source between 90 dB to 100 dB proven by measuring the value of Insertion Loss and Noise Reduction. There is no effect on the measurement when used two sources of sound.